2015
DOI: 10.1002/2014jb011563
|View full text |Cite
|
Sign up to set email alerts
|

Absolute gravity change associated with magma mass movement in the conduit of Asama Volcano (Central Japan), revealed by physical modeling of hydrological gravity disturbances

Abstract: The gravity signal originating from magma mass movement in a volcanic conduit is retrieved from the hydrologically disturbed absolute gravity data obtained at Asama Volcano (Central Japan) in 2004, using a three‐dimensional hydrological model. We improve the hydrological model of the previous study using realistic soil parameters and boundary conditions, to better estimate the spatiotemporal land‐water distributions and the consequent hydrological gravity disturbances. The newly estimated gravity disturbances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Suzuki (2002) interpreted these results to mean that the spring water discharged at the northern and eastern feet originates from the groundwater affected by the sulphate-chloride thermal water formed beneath the presently active crater, and that the groundwater flows to the 1370 Y. Usui et al northern and eastern feet along the surface of the collapsed caldera of Kurofu Volcano. Kazama et al (2015) also suggested that groundwater flows from the western side of Asama Volcano to the eastern flank through the volcanic conduit below the presently active crater. Furthermore, the helium isotope ratio of the hot spring water to the north of Line-C (Fig.…”
Section: N T E R P R E Tat I O N O F R E S I S T I V I T Y S T Ru Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Suzuki (2002) interpreted these results to mean that the spring water discharged at the northern and eastern feet originates from the groundwater affected by the sulphate-chloride thermal water formed beneath the presently active crater, and that the groundwater flows to the 1370 Y. Usui et al northern and eastern feet along the surface of the collapsed caldera of Kurofu Volcano. Kazama et al (2015) also suggested that groundwater flows from the western side of Asama Volcano to the eastern flank through the volcanic conduit below the presently active crater. Furthermore, the helium isotope ratio of the hot spring water to the north of Line-C (Fig.…”
Section: N T E R P R E Tat I O N O F R E S I S T I V I T Y S T Ru Cmentioning
confidence: 99%
“…Furthermore, there are several studies indicating the presence of high-water-content layer under Asama Volcano. Kazama et al (2015) calculated the steady distribution of the unconfined groundwater level around Asama Volcano based on hydrological physics. They revealed that the groundwater level around the summit area is about 1.5 km ASL and becomes higher to the west, which is consistent with the top of the conductive layer.…”
Section: N T E R P R E Tat I O N O F R E S I S T I V I T Y S T Ru Cmentioning
confidence: 99%
“…How this difference will affect the gravity observation is difficult to determine. It depends on the runoff and evaporation rates, as presented in an elaborate study of volcano gravity by absolute gravimeters [ Kazama et al ., ]. Nonetheless, we can qualitatively tell that the rainfall contribution is larger in the first observation, which cannot explain a 40 μGal increase in the second observation.…”
Section: Complex Environment In Tibet and Gravity Effectmentioning
confidence: 99%
“…Monitoring of the amount of material beneath the craters of active volcanoes provide valuable information for volcanological studies (Jachens & Eaton, 1980;Sanderson, 1982) and hazard assessment (Gottsmann et al, 2003) even if the deformation of volcano body is not measurable. Gravity surveying was conducted on different volcanoes to reveal the collapse of caldera (Furuya et al, 2003), detect the movement of magma in the conduit (Kazama et al, 2015;Okubo et al, 2013), or observe the drain-back process after the eruption (Watanabe et al, 1998). However, density monitoring of craters was not yet achieved due to the necessity of hundreds of sensors to provide a spatial resolution of a few tens of meters.…”
Section: Introductionmentioning
confidence: 99%